Diffuse hepatocellular carcinoma and splenic atrophy in a cirrhotic patient - Yusuf BAYRAKTAR,; Abdurrahman KADAYIFÇI,; Ferhun BALKANCI,; Şevket RUACAN,; Burhan KAYHAN, (Turkish Journal of Gastroenterology, 2020)
-